Extracts from The Book of Sarah. Issue 2 (1st December 2015) - Lightman, Sarah
Harry was born 23 December 2013. Beautiful, loud, hungry. Clock of my day. Emperor of my household. At a conference on motherhood in London in June 2015 I heard Bracha Ettinger speak about 'the three shocks of maternality'. It helped me to understand how much I am still recovering from my new reality.